Effects of oxytetracycline on denitrification and anammox processes in riparian buffer zone soil - Xue, Dongmei; Li, Jing; Yu, Hang; Jin, Ke; Wang, Zhongliang (International Journal of Agricultural and Biological Engineering, 2024)
Microbial denitrification and anaerobic ammonium oxidation (anammox) are two critical processes involved in nitrate (NO_3^-) removal from riparian buffer zones. However, the responses of these processes to antibiotics used in nearby animal farms are not yet fully understood. In this study the effects of oxytetracycline (OTC) short-term exposure on microbial denitrification and anammox in riparian buffer zones were examined via slurry-based 15N tracer technique combined with network analysis. Short-term OTC exposure will significantly decrease denitrification and anammox performance by restricting related functional genes, but inhibitory upper will appear at high OTC contents. The dominant bacterial community did not significantly change, while the bacterial network became more complex to keep the network stable. Functional bacteria containing nosZ and hzsB genes underwent significant changes, manifested as inhibitory effects, promotion effects, and no significant effects. The results indicated that short-term OTC exposure seemed unable to affect all types of functional bacteria, resulting in a considerable part of bacteria maintaining certain nitrogen removal performance. In the bacteria containing nosZ gene, it was found that 22.2% are denitrification mode bacteria and 77.8% are non-denitrification mode bacteria, suggesting that the restoration of the denitrification process should rely on the maintenance of a diverse denitrifying community. These results provide scientific knowledge on the effect of antibiotics-containing wastewater on the excessive N loading in aquatic ecosystems, and also indicate that additional efforts are needed to control antibiotic pollution in riparian buffer zones and coastal ecosystems. Keywords: riparian zone, oxytetracycline, denitrification, anammox, co-occurrence network, 15N tracerDOI: 10.25165/j.ijabe.20241706.8741Citation: Xue D M, Li J, Yu H, Jin K, Wang Z L. Effects of oxytetracycline on denitrification and anammox processes in riparian buffer zone soil. Int J Agric & Biol Eng, 2024; 17(6): 286–295.